2018
DOI: 10.1029/2018jb016289
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Evaluation of Fault Sources Based on Paleoseismic Evidence From Mass‐Transport Deposits: The Example of Aysén Fjord, Chile

Abstract: Contemporaneous mass‐transport deposits (MTDs) recorded in lake and fjord sediments provide evidence of past seismic shaking. However, because they are usually not connected to a fault rupture, assessment of the earthquake source remains difficult. Based on observed coseismic mass wasting and associated seismic shaking, previous studies assigned minimum intensities required to trigger them. Attempts to infer their earthquake source relied on methods developed to estimate the location and magnitude of historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 56 publications
(133 reference statements)
1
30
0
Order By: Relevance
“…As a consequence, all seismo-turbidites that consist solely of deltaic material and are not associated with onshore landslides, that is, all except SL-G, SL-F, SL-D, and the youngest EM3 turbidite, are considered associated to megathrust earthquakes, bringing the total number of megathrust-earthquake related turbidites to 24. This is in agreement with previous research that already linked events SL-G, SL-F, and SL-D to crustal earthquakes and SL-EF and SL-DE to megathrust earthquakes (Vanneste et al, 2018;Wils et al, 2018). However, it is important to note that some far-field crustal (such as the 1927 earthquake) or intraslab earthquakes may have a similar effect in terms of seismic shaking on the fjord as megathrust earthquakes, resulting in the same turbidite signal in the sediment core.…”
Section: Crustal-versus Megathrust-earthquake-induced Depositssupporting
confidence: 94%
See 3 more Smart Citations
“…As a consequence, all seismo-turbidites that consist solely of deltaic material and are not associated with onshore landslides, that is, all except SL-G, SL-F, SL-D, and the youngest EM3 turbidite, are considered associated to megathrust earthquakes, bringing the total number of megathrust-earthquake related turbidites to 24. This is in agreement with previous research that already linked events SL-G, SL-F, and SL-D to crustal earthquakes and SL-EF and SL-DE to megathrust earthquakes (Vanneste et al, 2018;Wils et al, 2018). However, it is important to note that some far-field crustal (such as the 1927 earthquake) or intraslab earthquakes may have a similar effect in terms of seismic shaking on the fjord as megathrust earthquakes, resulting in the same turbidite signal in the sediment core.…”
Section: Crustal-versus Megathrust-earthquake-induced Depositssupporting
confidence: 94%
“…Previous research in Aysén Fjord (Van Daele et al, 2013;Vanneste et al, 2018;Wils et al, 2018) has shown that its sediments are a valuable archive for paleoseismological research, with a particular focus on crustal earthquakes due to its location on the LOFZ (Figure 1b). Traces of the 2007 Aysén earthquake were identified on high-resolution bathymetric and seismic data covering the inner part of the fjord, together with nine older seismic-stratigraphic levels (termed SL-A, SL-B, SL-C, SL-CD, SL-D, SL-DE, SL-EF, SL-F, and SL-G) characterized by the presence of seismically triggered MTDs related to fjord wall collapses and/or subaqueous landslides (Van Daele et al, 2013;Wils et al, 2018).…”
Section: Aysén Fjord As Paleoseismic Recordermentioning
confidence: 99%
See 2 more Smart Citations
“…Deltas, formed from unconsolidated material, are very sensitive to failure by an external trigger such as seismic shaking (Girardclos et al, 2007;Hasiotis et al, 2006;Hilbe & Anselmetti, 2014;Leithold et al, 2018). Furthermore, the potential for delta failures to generate significant tsunamis during strong shaking events (Vanneste et al, 2018) has been documented at sites with diverse climatic conditions, such as Alaska (USA; Field et al, 1982;Parsons et al, 2014) and Haiti (Hornbach et al, 2010).…”
Section: The Role Of Coastal Landslides In the Palu Tsunamismentioning
confidence: 99%